ROLE OF KSHARSUTRA IN THE TREATMENT OF RECURRENT PILONIDAL SINUSES - R. Badwe, *Yogesh; Rokade, Bharat; Paliwal, Amit (International Journal of Ayurveda and Pharma Research, 2016)
Pilonidal sinus is a disease that most commonly arises in the hair follicles of the natal cleft of the sacrococcygeal area. Incidence is reportedly 26 per 1000 population, affecting males twice as often as females and predominantly young adults of working age. Pilonidal sinus usually presents as an abscess or a chronically discharging, painful sinus tract. Irrespective of the mode of presentation the painful nature of the condition causes significant morbidity, often with a protracted loss of normal activity. The ideal therapy would be a quick cure that allowed patients to return rapidly to normal activity, with minimal morbidity and a low risk of complications. As recurrence rate after surgery is very high almost 50 % and 30 % after surgery, this needs to see another treatment modalities. Ksharasutra has proved its efficacy in the treatment of fistula-in-ano since many decades. So here we have considered Ksharsutra for the treatment of recurrent pilonidal sinus especially in the recurrence after surgery. In this study very good results were found with post treatment follow up. In this study of 34 patients, all had achieved complete healing within 4 weeks to 8 weeks, mean is 6 weeks of operation. Follow-up of 30 patients was available for 12â€“24 months in which no patients had recurrence.